Physiological and Behavioral Factors in Musicians’ Performance Tempo - Wright, Shannon E.; Palmer, Caroline (Frontiers in Human Neuroscience, 2020)
Musicians display individual differences in their spontaneous performance rates (tempo) for simple melodies, but the factors responsible are unknown. Previous research suggests that musical tempo modulates listeners’ cardiovascular activity. We report an investigation of musicians’ melody performances measured over a 12-hour day and subsequent changes in the musicians’ physiological activity. Skilled pianists completed four testing sessions in a single day as cardiac activity was recorded during an initial five minutes of baseline rest and during performances of familiar and unfamiliar melodies. Results indicated slower tempi for familiar and unfamiliar melodies at early testing times. Performance rates at 09h were predicted by differences in participants’ alertness and musical training; these differences were not explained by sleep patterns, chronotype, or cardiac activity. Individual differences in pianists’ performance tempo were consistent across testing sessions: participants with a faster tempo at 09h maintained a faster tempo at later testing sessions. Cardiac measures at early testing times indicated increased heart rates and more predictable cardiac dynamics during music performance than baseline rest, and during performances of unfamiliar melodies than familiar melodies. These findings provide the first evidence of cardiac dynamics that are unique to music performance contexts.